Early Prediction of Diabetes Using Deep Learning Convolution Neural Network and Harris Hawks Optimization - R, Murugadoss (International Journal of Integrated Engineering, 2021)
Owing to the gravity of the diabetic disease the minimal level symptoms for diabetic failure in the early stage must be forecasted. The prediction system instantaneous and prior must thus be developed to eliminate serious medical factors. Information gathered from Pima Indian Diabetic dataset are synthesized through a profound learning approach that provides features for diabetic level information. Metadata is used to enhance the recognition process for the profound learned features. The distinct details retrieved by integrated machine and computer technology, including glucose level, health information, age, insulin level, etc. Due to the efficacious Hawks Optimization Algorithm (HOA), the data's insignificant participation in diabetic diagnostic processes is minimized in process analysis luminosity. Diabetic disease has been categorized with Deep Learning Convolution Networks (DLCNN) from among the chosen diabetic characteristics. The process output developed is measured on the basis of test results in terms of error rate, sensitivity, specificity and accuracy.